KORELASI ANTARA SIKAP SISWA TERHADAP HASIL BELAJAR FISIKA PADA SISWA KELAS X SMA LABSCHOOL UNTAD - Khairiyah , Yaumil; Ali, Muhammad (Universitas Tadulako, 2021)
This study aims to determine whether there is a correlation between students' attitudes towards physics learning outcomes in class X Lab School UNTAD students. This research is a descriptive research, the approach used in this research is a quantitative approach, and analyzed with statistics and the results are described. Respondents in this study were students of class X MIA B SMA Lab School UNTAD. The instrument used was a questionnaire on student attitudes in learning physics which amounted to 48 numbers with 34 positive statements and 14 negative statements and for the learning outcomes instrument using an objective test of 25 numbers. The results of the correlation analysis for each aspect of the attitude have a positive relationship with the value of r = 0.360. The contribution of students' attitudes is indicated by the coefficient of determination of 12.96%, while the rest is influenced by other factors that are not the object of research. Based on the results of the research analysis, it can be concluded that the relationship between each variable of students' attitudes in learning physics with learning outcomes in physics is significant and the direction is positive.